Topsy and Tim meet the firefighters - Adamson;Jean (London Ladybird, 2007)
Topsy and Tim find fun and adventure in the real world. Their engaging stories are reassuring for young children having first experiences of their own. In Topsy and Tim Meet the Firefighters, the twins have an exciting day out at the fire station! They get to see all the fire appliances and learn about fire safety